Does the international financial system discriminate against developing countries? - Graham Bird (Intereconomics, 1988)
The last 15 years have seen broad operational changes in the international system, accompanied since the beginning of the 1980s by a change in economic philosophy in a number of important industrial countries. Professor Bird examines the effects of various features of the post-Bretton Woods era on developing countries and proposes some reforms for the future.
Keywords: 330; International Financial Reform